Online Marketing Strategy of Hydroponic Green Curly Lettuce on MSME Riyan Farm Serang, Banten - Deriska Chaerunnisa; Mudatsir Najamuddin; Fadeli Muhammad Habibie (Program Studi Agribisnis UIN Syarif Hidayatullah Jakarta, 2022)
MSME Riyan Farm is a hydroponic green curly lettuce cultivation business unit in Serang, Banten that markets its product online through social media. The right marketing can determine the volume of sales and affect the company's profits so it requires a strategy. This study aims to determine the factors of strength and weakness, opportunities and threats, company position, alternatives, and appropriate marketing strategy priorities in increasing hydroponic green curly lettuce sales at MSME Riyan Farm Serang, Banten by using SWOT and QSPM Matrix analysis tools. The type of research used is descriptive-analytical. The results of the research through the Input Phase (EFE and IFE Matrix), Matching Phase (IE and SWOT Matrix), and Decision Making Phase (QSPM Matrix), that the value of IFE = 2.90 and EFE = 3.37 with the company's position in Cell II (Growth and Development) which supports aggressive growth policy (market development strategy, product development, market penetration, backward integration, forward integration, horizontal integration). With strategic priority, namely to establish marketing cooperation with similar companies with STAS = 6,321. Therefore, companies must optimize the use of social media to identify product identities to expand market share, supported by competent human resources in the field of digital marketing.Keywords: online marketing strategy; green curly lettuce; hydroponic AbstrakMSME Riyan Farm merupakan unit usaha budidaya selada keriting hijau hidroponik di Kota Serang, Banten yang memasarkan produknya secara daring melalui media sosial. Pemasaran yang tepat dapat menentukan volume penjualan dan mempengaruhi keuntungan perusahaan sehingga membutuhkan strategi. Penelitian ini bertujuan untuk mengetahui faktor kekuatan dan kelemahan, peluang dan ancaman, posisi perusahaan, alternatif dan prioritas strategi pemasaran yang tepat dalam meningkatkan penjualan selada keriting hijau hidroponik pada MSME Riyan Farm Serang, Banten dengan menggunakan alat analisis Matriks SWOT dan QSPM. Jenis penelitian yang digunakan adalah deskriptif analitis. Hasil penelitian melalui Tahap Input (Matriks EFE dan IFE), Pencocokan (Matriks IE dan SWOT), dan Pengambilan Keputusan (Matriks QSPM), bahwa nilai IFE=2.90 dan EFE=3.37 dengan posisi perusahaan pada Sel II (Tumbuh dan Berkembang) yang mendukung kebijakan pertumbuhan agresif (strategi pengembangan pasar, pengembangan produk, penetrasi pasar, integrasi kebelakang, integrasi kedepan, integrasi horizontal). Dengan prioritas strategi yaitu menjalin kerjasama pemasaran dengan perusahaan sejenis dengan STAS=6.321. Maka dari itu perusahaan harus pengoptimalkan pemanfaatan media sosial dalam upaya pengenalan identitas produk guna memperluas pangsa pasar dengan didukung oleh sumber daya manusia yang kompeten dibidang pemasaran digital.Kata kunci: strategi pemasaran daring; selada keriting hijau; hidroponik